Políticas linguísticas para indígenas em contexto urbano: uma proposta de análise a partir da Região Metropolitana de São Paulo (SP) - Silva, Diego Barbosa da (2024)
The latest censuses carried out in Brazil point to a sharp growth in the self-declared indigenous population in urban areas. Whether due to migration or awareness of their identity, data reveal that today many indigenous people live in urban contexts struggle to maintain their traditions and cultures. Parallel to this, after acquiring the right to land and a differentiated culture in the 1988 Constitution, it is possible to observe that indigenous peoples, through their mobilizations and struggles, have produced waves of language policies in Brazil. These are waves that produce acquisition, status, corpus and structuring language policies designed to create actions for the teaching, use, documentation, co officialization and preservation of indigenous languages throughout the country. Therefore, this research aims to study language policies for indigenous people in an urban context and, consequently, draw attention to the fact that many indigenous people live in large cities and need their rights, including linguistic, to be ensured by government actions and policies. To do this, we look at the Metropolitan Region of São Paulo, the largest metropolis in South America, which presents a notably complex indigenous situation, with the Guarani Mbya people living on indigenous lands and more than 50 peoples living in an urban context, dispersed throughout the municipalities of the region, claiming for their rights. Through research on government websites and through we consult responses to formal inquiries we carried out a survey of language policies for indigenous people of this metropolis in order to build a catalog of policies, which constitutes the product of our professional master's degree.